The approach to a problem of delay and cancellations of trips of civil aircraft - Махди Яхья, Альгабри Табит (Proceedings of National Aviation University (archive), 2000)
The problem of delay and cancellations of trips of civil aircraft is considered. The analysis of the factors is conducted, which account is necessary for it of solution, the paths of solution are scheduled